2022
DOI: 10.2169/internalmedicine.8256-21
|View full text |Cite
|
Sign up to set email alerts
|

A Rare Presentation of a Compression Fracture or a Typical Presentation of Lateral Cutaneous Nerve Entrapment Syndrome: A Diagnostic Error?

Abstract: A 78-year-old woman complained of severe pain in the left costal region. Her body mass index was 23.1 kg/m 2 . Lateral cutaneous nerve entrapment syndrome (LACNES) was the suspected diagnosis because the affected area was 2×2 cm and positive for pinch sign. Seventeen days later, the patient again presented with complaints of lower back pain accompanied by back pain upon extending the spine. Magnetic resonance imaging of the spine showed a fracture of the vertebral body of T11. We herein discuss our errors in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…These syndromes also have several common features: prevalence in women aged 20–50 years, right-sided dominance (except for POCNES), and frequent involvement of lower thoracic spine levels, including Th11 (Th7–12) [ 2 4 ] . Previous studies have reported that more than one of these syndromes can develop in the same patient [ 5 ] , so the occurrence of three cutaneous nerve entrapment syndromes in this patient is possible.…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…These syndromes also have several common features: prevalence in women aged 20–50 years, right-sided dominance (except for POCNES), and frequent involvement of lower thoracic spine levels, including Th11 (Th7–12) [ 2 4 ] . Previous studies have reported that more than one of these syndromes can develop in the same patient [ 5 ] , so the occurrence of three cutaneous nerve entrapment syndromes in this patient is possible.…”
Section: Discussionmentioning
confidence: 82%
“…Differentiating nerve entrapment syndrome from vertebral compression fractures is difficult. Endo et al described a case of Th11 vertebral compression fracture that was initially misdiagnosed as a combination of LACNES and ACNES at the level of Th11 [ 5 ] . In their patient, the pain improved following trigger-point injections, but the abdominal pain repeatedly recurred within approximately a week, and back pain developed about a month after the initial pain.…”
Section: Discussionmentioning
confidence: 99%